Diamonds are forever - Fleming, Ian, 1908-1964 (Fleming, Ian, 1908-1964. James Bond 007., 2012)
British secret agent James Bond assumes the identity of a captured courier and solicits the help of gorgeous Tiffany Case, the diamond smugglers' American go-between.